Perencanaan Kebutuhan Pranata Laboratorium Pendidikan di Institut Pertanian Bogor: Requitment Planning of Laboratory Education Staff at Bogor Agricultural University - Eko Prasetyo; M. Syamsul Maarif; Komar Sutriah (IPB University, 2016)
The objective of the research was to analyze requirement planning, ideal number as well as formulating planning strategy for Laboratory Education Staff (LES) at Bogor Agricultural University. Data was collected by filling the questionnaire and interview with laboratory staff of Bogor Agricultural University, then documentation. Completely randomized design and Antilon (anti-ln/enilai y) was performed to analyze the data, then geometric mean value was analysed by qualitative descriptive, whereas formulation of strategy was performed by SWOT matric. The result shows that time activities allocation by LES were still low as well as less ideal number of LES. In addition, according to SWOT matric analysis, formulation of the strategies to improve work quality of LES were development of staff capability, providing adequate tools and materials, escalating of staff performance and refinement of leadership manner.